Predictors of Patient-Reported Financial Hardship in Patients Hospitalized With Critical Illness and Its Association With Patient Outcomes - Uyeda, Alison M.; May, Peter; Pytel, C. Clare; Nielsen, Elizabeth L.; Engelberg, Ruth A.; Khandelwal, Nita (CHEST critical care, 2025)
A high burden of financial hardship has been demonstrated in critically ill patients. Understanding the sociodemographic and clinical risk factors for financial hardship and its association with patient outcomes can help to guide future interventions to mitigate financial hardship in this patient population. What are the sociodemographic and clinical risk factors for financial hardship in critically ill patients and its association with patient-reported outcomes? This prospective cohort study enrolled adults with chronic, life-limiting illness, acute severe illness, or both hospitalized in the ICU. Twenty-six sociodemographic and clinical variables were measured using electronic health record or patient questionnaire data collected at either 1 or 3 months after ICU admission. Risk factors for patient-reported financial hardship were evaluated using linear regression. The association between financial hardship and 4 patient-reported outcomes was tested with probit and linear regression. We enrolled 171 patients with a median are of 58 years (interquartile range, 25 years), including 64 female (37%), and 44 patients (26%) from racial or ethnic minority groups. Illness-related change in work status (β = 3.5; P = .02) and poorer self-reported health status (β = 2.4; P = .003) were associated with greater patient-reported financial hardship. Higher education level (β = –2.6; P = .001) was associated with less financial hardship. Higher financial hardship was associated with all 4 patient-reported outcomes (P < .001): feelings of depression (β = 0.2) and anxiety (β = 0.3), poorer quality of life (β = 0.04), and lower emotional preparedness for the future (β = 0.05). This study demonstrated an association between patient-reported financial hardship and negative patient-reported outcomes in critically ill patients. Our findings also highlight important risk factors for financial hardship and suggest that sociodemographic factors, including education level, illness-related change in work status, and poorer self-reported health status, could contribute more than clinical factors. Our findings provide a foundation for future development of screening tools and interventions to mitigate financial hardship in critically ill patients.